Risk factors for Crimean-Congo Haemorrhagic Fever (CCHF) virus exposure in farming communities in Uganda - Atim, Stella A.; Ashraf, Shirin; Ademun, Anna R.; Nakayiki, Teddy; Balinandi, Stephen; Nakanjako, Gladys; Abaasa, Andrew; Odongo, Steven; Esau, Martin; Kaleebu, Pontiano; Lutwama, Julius J.; Masembe, Charles; et al. (Journal of Infection, 2022)
Crimean-Congo Haemorrhagic Fever (CCHF) is an emerging human-health threat causing sporadic outbreaks in livestock farming communities. However, the full extent and the risks associated with exposure of such communities has not previously been well-described. We collected blood samples from 800 humans, 666 cattle, 549 goats and 32 dogs in districts within and outside Ugandan cattle corridor in a cross-sectional survey, and tested for CCHFV-specific IgG antibodies using Enzyme-Linked Immunosorbent Assays. Sociodemographic and epidemiological data were recorded using structured questionnaire. Ticks were collected to identify circulating nairoviruses by metagenomic sequencing. CCHFV seropositivity was in 221/800 (27·6%) in humans, 612/666 (91·8%) in cattle, 413/549 (75·2%) in goats and 18/32 (56·2%) in dogs. Human seropositivity was associated with livestock farming (AOR=5·68, p<0·0001), age (AOR=2·99, p=0·002) and collecting/eating engorged ticks (AOR=2·13, p=0·004). In animals, seropositivity was higher in cattle versus goats (AOR=2·58, p<0·0001), female sex (AOR=2·13, p=0·002) and heavy tick infestation (>50 ticks: AOR=3·52, p=0·004). CCHFV was identified in multiple tick pools of Rhipicephalus appendiculatus.
Keywords: Viral Haemorrhagic Fever; Crimean-Congo Hemorrhagic fever virus; CCHF; zoonotic disease